An Analysis of Bipolar Trapezoidal Neutrosophic Sets (BTNSs) for Examining the Income-Increasing and Poverty-Reduction Effects of Ecological Compensation in the Huai River Basin of Anhui Province: A Comprehensive Study - Shengnan Zhang; Yuwei Wang (Neutrosophic Sets and Systems)
This study proposes the decision-making approach for evaluation of ecological compensation in the Huai river basin of Anhui province. We used the neutrosophic sets to deal with the uncertainty information. In both the trapezoidal and bipolar neutrosophic environments, decision makers supply all the information needed to make decisions in complex multicriteria decision-making problems. This work suggests a novel, efficient method to handle these situations. We used two methods to evaluate the criteria and alternatives such as LMAW and MARCOS. We used the LMAW method to compute the criteria weights and the MARCOS method to rank the alternatives. Nine criteria and eleven alternatives are evaluated in this study. The sensitivity analysis is conducted to show the stability of the results. The outcomes show the rank of the alternative is stable.